Effects of Marantodes pumilum (Kacip Fatimah) on vaginal pH and expression of vacoular ATPase and carbonic anhydrase in the vagina of sex-steroid deficient female rats - Giribabu, Nelli; Karim, Kamarulzaman; Salleh, Naguib (Elsevier, 2018)
Background: In sex-steroid deficiency, increased in the pH of vaginal fluid is due to low estrogen levels. Hypothesis: Consumption of Marantodes pumilum leaves helps to ameliorate increased in vaginal fluid pH in sex-steroid deficient condition. Purpose: To investigate changes in vaginal fluid pH and expression of proteins that participate in pH changes i.e vacoular (V)-ATPases and carbonic anhydrases (CA) in the vagina following M. pumilum leaves consumption. Methods: Ovariectomized adult female rats were treated orally with M. pumilum leaves extract (MPE) at 100, 250 and 500 mg/kg.b.w and estradiol at 0.2 µg/kg/b.w for 28 days. At the end of the treatment, vaginal fluid pH was measured in anesthetised rats by using micropH probe. Following sacrificed, levels of V-ATPase and CA proteins and mRNAs in the vagina were identified by Western blotting and real-time PCR, respectively. Protein distribution was visualized by immunohistochemistry. Results: Administration of MPE causes the pH of vaginal fluid to decrease and expression and distribution of vaginal V-ATPase A & B and CA II, III, IX, XII and XIII to increase. Conclusions: The decrease in vaginal fluid pH following MPE treatment suggested that this herb has potential to be used to ameliorate vaginal fluid pH changes in sex-steroid deficient condition.